Interpopulation Variation in the Atlantic Salmon Microbiome Reflects Environmental and Genetic Diversity - Tamsyn Uren Webster (Applied and Environmental Microbiology, 2018)
The microbiome has a crucial influence on host phenotype, and is of broad interest to ecological and evolutionary research. Yet, the extent of variation that occurs in the microbiome within and between populations is unclear. We characterised the skin and gut microbiome of seven populations of juvenile Atlantic salmon (Salmo salar) inhabiting a diverse range of environments, including hatchery-reared and wild populations. We found shared skin OTUs across all populations and core gut microbiota for all wild fish, but the diversity and structure of both skin and gut microbial communities were distinct between populations. There was a marked difference between the gut microbiome of wild and captive fish. Hatchery-reared fish had lower intestinal microbial diversity, lacked core microbiota found in wild fish, and showed altered community structure and function. Captive fish skin and gut microbiomes were also less variable within populations, reflecting more uniform artificial rearing conditions. Surrounding water influenced the microbiome of the gut and, especially, the skin, but could not explain the degree of variation observed between populations. For both the gut and skin, we found that there was greater difference in microbial community structure between more genetically distinct fish populations, and also that population genetic diversity was positively correlated with microbiome diversity. However, diet is likely to be the major factor contributing to the large differences in gut microbiota between wild and captive fish. Our results highlight the scope of inter-population variation in the Atlantic salmon microbiome, and offer insights into the deterministic factors contributing to this.